Spiciness anomalies in the upper North Pacific based on Argo observations - Wang, Tong; Suga, Toshio; Kouketsu, Shinya (Frontiers in Marine Science, 2022)
The density-compensated salinity anomalies (spiciness anomalies) in the upper North Pacific were investigated using Argo float profiles during 2004–2018. The freshening of the subtropical thermocline was found within the Central Mode Water (CMW) and the North Pacific Intermediate Water (salinity minimum). Meanwhile, the increasing of salinity was found in the lighter layer within the North Pacific Tropical Water (salinity maximum). The interannual and longer spiciness anomalies were interpreted with three-dimensional evolutions and were linked to the fate of three mode waters (i.e., Subtropical Mode Water (STMW), Eastern Subtropical Mode Water (ESTMW), and CMW) for the first time. In the STMW, the salinity was dominated by a quasi-decadal variability, which was consistent with the KE variability with a 1-year lag, and did not show rapid freshening. In the CMW, the salinity decreased with a quasi-decadal variability, which was weaker and out of the phase compared with the STMW. In the ESTMW, the salinity was dominated by year-to-year variability. The spiciness anomalies originated mainly in the outcrop region of the isopycnals, where they were accompanied by the formation and the subduction of the mode waters. They were also propagated and decayed downstream the geostrophic currents. However, a few of the interannual anomalies found in the northern part of the CMW were almost dampened before their spread further south. In addition, some anomalies in the ESTMW appeared and intensified without a connection to the mixed layer. These anomalies occurred far from the outcrop line, suggesting the effects were caused likely by a salt-finger that is related to the modification of the mode waters. Furthermore, the propagation of the spiciness anomalies in the western to the central subtropics was significantly faster than the geostrophic current and inclined to the inner side of streamlines. These indicated the transport by eddies in addition to geostrophic current.